The Use of a Genre-Based Approach to Promote Writing Skills through Instructional Texts in a Colombian 11th EFL Classroom (2019)
Genre-based approach is a pedagogy that focuses on literacy placing texts as the central core of the learning process. It focuses on texts as the main unit to convey meaning and increases the awareness of students regarding an approach that measures the evolution of their meaning-making through a tool based on communication and pedagogy (Herazo, 2012; Swales, 1999). This study sought to describe the impact of the implementation of instructional texts to influence the development of writing skills among 11th EFL graders from a high school located in Sincelejo. This qualitative action-case study gathered data through a diagnostic instrument, students’ reflective journals, surveys, focus groups, and artifacts. Data analysis procedures were conducted through content analysis, discourse analysis, codification and triangulation principles. The intervention plan counted on the implementation of instructional texts and an online videogame called “Papa’s Pizzeria” that has a context based on daily life issues, as it is buying a pizza, and that follows a pattern in telling players what to do and how to do it. The results aimed at contributing to the development of students’ writing skills in a public high school using genre-based approach and video games. In a near future, this study will serve as a starting point to generate a new perspective on how to use texts to teach writing.